Pengaruh ESG Disclosure, Green Investment, dan Eco-Efficiency terhadap Nilai Perusahaan: Studi pada Perusahaan Indeks IDX ESG Leaders (2020-2024) - Anisa Alpha Salsabila (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study examines the effects of ESG disclosure, green investment, and eco-efficiency on the firm value of companies included in the IDX ESG Leaders Index, with 55 observations over the 2020–2024 period. Sustainability practices are increasingly drawing the attention of companies and investors because they are believed to enhance market confidence and firm value, although previous research has yielded inconsistent findings. A quantitative approach with a causal design was used in this study, utilizing secondary data. The sample was selected using purposive sampling, resulting in 11 companies as research subjects and 55 observations. The data were analyzed using panel data regression with the REM model. The results indicate that ESG Disclosure has a positive and significant effect on firm value, while Green Investment and Eco-Efficiency have negative and significant effects on firm value. Furthermore, all three variables have a significant simultaneous effect on firm value. These findings suggest that ESG disclosure receives a positive response from investors, whereas Green Investment and Eco-Efficiency have not yet fully created firm value, while also enriching the empirical evidence regarding the implementation of sustainability aspects within the Indonesian capital market.